Регистрация
Войти
Стать экспертом Правила
Алгебра

(x^2−12x+20)^2=(x^2+2x−12)^2

ОТВЕТЫ

Объяснение:

(x^2-12x+20)^2=(x^2+2x-12)^2\\(x^2+2x-12)^2-(x^2-12x+20)^2=0\\(x^2+2x-12-x^2+12x-20)*(x^2+2x-12+x^2-12x+20)=0\\(14x-32)*(2x^2-10x+8)=0\\(14x-32)*2*(x^2-5x+4)=0\ |:2\\(14x-32)*(x^2-5x+4)=0\\(14x-32)*(x^2-4x-x+4)=0\\(14x-32)*(x*(x-4)-(x-4))=0\\(14x-32)*(x-4)*(x-1)=0\\14x-32=0\ |:14\\x_1=\frac{16}{7}\\x-4=0\\x_2=4\\x-1=0\\x_3=1.

: x₁=16/7; x₂=4; x₃=1.

233
Контакты
Реклама на сайте
Спрошу
О проекте
Новым пользователям
Новым экспертам